2019
DOI: 10.3390/en12203939
|View full text |Cite
|
Sign up to set email alerts
|

Cuttings Transport Using Pulsed Drilling Fluid in the Horizontal Section of the Slim-Hole: An Experimental and Numerical Simulation Study

Abstract: Poor transport of cuttings in horizontal sections of small-bore well holes leads to high torque and increases the risk of the drill becoming stuck, reducing its service life and posing a threat to safe operation. Because the conventional cuttings transport method cannot effectively remove the cuttings bed, a transport method using pulsed drilling fluid based on a shunt relay mechanism is proposed. A three-layer numerical simulation model of cuttings transport in horizontal small-bore wells is established. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…When the flow velocity is large enough, under the influence of fluid-lift and radial pulsation, the exchange of momentum and mass occurs simultaneously among the layers of solid particles. Finally, the solid particles enter the state of suspension and migration, as shown in Figure 4 [16][17][18]. When the DDG method are used, the solid particles such as NGH and sediment are transported in inner pipe of double-layer continuous pipe in the horizontal section.…”
Section: Slurry Migration State In Different Methodsmentioning
confidence: 99%
“…When the flow velocity is large enough, under the influence of fluid-lift and radial pulsation, the exchange of momentum and mass occurs simultaneously among the layers of solid particles. Finally, the solid particles enter the state of suspension and migration, as shown in Figure 4 [16][17][18]. When the DDG method are used, the solid particles such as NGH and sediment are transported in inner pipe of double-layer continuous pipe in the horizontal section.…”
Section: Slurry Migration State In Different Methodsmentioning
confidence: 99%
“…Effective erosion of the cuttings-bed has major influence on the cleaning efficiency, it has been demonstrated that loose and porous cuttings-beds are easier to clean as single cuttings particles can move freely into the bed, on the other hand, well consolidated cuttings-bed are more complex to clean as the cuttings particles are embedded into the bed and there are not loose particles to move [51]. It has been shown [21,27,55] that to disturb the cuttings at rest and erode the cuttings bed, it is necessary to reach the critical velocity, and it was discussed, that smaller cuttings particles are easier to erode from the cuttings bed.…”
Section: Cuttings Settling Velocity and Erosionmentioning
confidence: 99%
“…The pulse parameters set under the experimental conditions in th in Table 2 [40]. As shown in Figure 10, with the same q and pulse am…”
Section: Sensitivity Analysis Of Pulse Parametersmentioning
confidence: 99%
“…The pulse parameters set under the experimental conditions in this study are listed in Table 2 [40]. As shown in Figure 10, with the same q and pulse amplitude ratio, the cuttings bed movement distance decreases as the pulse period increases.…”
Section: Sensitivity Analysis Of Pulse Parametersmentioning
confidence: 99%